Lactate/albumin ratio as a prognostic biomarker for in-hospital mortality in pediatric patients with necrotizing enterocolitis - Ban Li; Yuanzhi Chen; Zhen Yang; Xianglun Sun; Cheng Tian; Jingsi Liu; Lihua Yuan; Kanglin Dai (BMC Pediatrics)
Abstract Objective To assess the lactate/albumin ratio (L/A) as a prognostic biomarker for differentiating in-hospital mortality risk in pediatric patients with necrotizing enterocolitis (NEC). Methods We performed a retrospective study utilizing the Pediatric Intensive Care (PIC) database. Patients diagnosed with NEC were categorized into a discharge group and a death group based on in-hospital outcomes. The association between L/A and in-hospital mortality was assessed using logistic regression models. Results After inclusion and exclusion criteria, 100 NEC patients were included in the study, with 87 survivors and 13 deaths. The mean age at admission was 21.6 ± 2.4 days, and the mean weight was 2.1 ± 0.1 kg. Significant differences in creatinine, international normalized ratio (INR) and L/A were observed between the groups (p < 0.05). The L/A ratio was a substantial predictor of in-hospital mortality, with an odds ratio (OR) of 5.24 (95% CI: 1.51–18.20, p = 0.01). An L/A cutoff value of 0.56 demonstrated a sensitivity of 0.923 and specificity of 0.486, with an AUC of 0.725 from the ROC curve analysis. Patients with an L/A ratio of ≥ 0.56 had a higher risk of in-hospital mortality (OR = 11.35, 95% CI: 1.40-91.93, p = 0.02). Conclusion Our study suggested that the L/A ratio may serve as a reliable prognostic indicator for in-hospital mortality in NEC. However, given the limitations of our research, more prospective studies are still needed in the future to test the predictive value of L/A ratio for the prognosis of NEC disease. Clinical trial number Not applicable.